Obtenção de produtos de conversão da glicerina por tratamento com catalisadores de nióbio e suas caracterizações por RMN - Poliane Chagas (2015)
This dissertation mainly focuses on the use Nuclear Magnetic Resonance (NMR) in the structural elucidation of organic compounds, which constitute a complex mixture that was obtained from the conversion of commercial glycerin under reactions catalyzed by niobium-modified silicates. Three different catalytic materials have been synthesized and the reactions involved tetraethoxysilane (TEOS) polymerization as source of silicon in the presence of different niobium salt quantities along with cetyltrimethylammonium bromide supramolecular arrangements, which have been used as structural frames. The obtained materials have been characterized by several techniques, including X-ray diffraction (XRD), electronic transmission microscopy (TEM) coupled to X-ray dispersive energy detector (EDS) and adsorption/desorption of N2. The characterization tests indicated that the obtained materials presented high specific areas (Cat1, 1069 m2.g-1; Cat2, 555 m2.g-1 e Cat3, 486 m2.g-1), suggesting their potential usefulness in acid-catalysis reactions. The glycerol conversion reactions have been carried out on a batch reactor, the three catalysts synthesized in three reaction systems were tested. The set catalyst / reaction system showed a higher yield against the allyl alcohol had their products analyzed by NMR. In order to determine the identity of a greater number of compounds obtained during these reactions, the obtained set of volatile compounds has previously been submitted to column distillation and seven fractions have then been obtained. Each of these seven fractions has been analyzed by 1D and 2D NMR spectroscopy. 2D NMR gives information on chemical vicinities and allows a greater dispersion of resonances in comparison with the 1D spectra. Nevertheless the distillation allowed to avoid several signal overlapping issues and the spectra obtained for the seven fractions were easier to analyze in comparison with the respective spectra obtained for the product prior to distillation. Were elucidated the twenty substances structures in fraction 1, eighteen in fraction 2, thirteen in fraction 3, eleven in fraction 4, ten in the fraction 5 and eleven in fraction 6, being that in total, were elucidated the structures of 27 substances. The CG-MS analysis have pointed the most efficient reaction, which have assured 80 % of glycerin conversion as well as a high yield and selectivity in allyl alcohol production.